Teologi Pembebasan Ali Syari’ati (Kajian Humanisme dalam Islam) - Siti Syamsiyatul Ummah ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2019)
The article describes the liberation theology of Ali Syari'ati with an Islamic humanism approach. As a leading Muslim thinker in the modern age, Ali Syari'ati's role in fighting the oppression of Pahlevi's regime was enormous. He appeared as a propagator that encouraged the young generation in Iran around the 1970ish to take a stance and combat Syah Pahlevi's authoritarian and oppressive regime. The article used a qualitative method with a literature review of the liberation theology perspective of Ali Syari'ati that strive for humanity to liberate the people from the authoritarian regime. The article showed that Ali Syari'ati succeeded in establishing a revolutionary Islamic ideology with tawhid as the foundation. Its revolution aimed to enhance the status of and promote egalitarianism among human beings. According to Ali Syari'ati, tawhid is a unity between God, humans, and the universe. Therefore, any social discrimination, injustice, tyranny, and oppression should be fought back based on liberation theology. The research also showed that Ali Sya'riati's view of religious humanism succeeded in urging the people on negating dualism between the ruling and bourgeois class, which eventually created awareness in each human of the position as God's representative on earth.